2019
DOI: 10.1038/s41598-018-36759-5
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed bimetallic Au@Pt nanoparticles for glucose oxidation

Abstract: Bimetallic nanoparticles (NPs) have aroused interest in various fields because of their synergetic and unique properties. Among those nanoparticles, we strategically approached and synthesized Au@Pt NPs via the sonochemical method with different molar ratios (e.g. 3:7, 5:5, and 7:3) of Au to Pt precursors. The particle structure was confirmed to be core-shell, and the size was estimated to be 60, 52, and 47 nm, respectively, for 3:7, 5:5, and 7:3 ratios of Au to Pt. The detailed structure and crystallinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…These structural findings were confirmed by analysis of XRD standard Bragg reflections (Fig. 2b), which could be assigned to fcc gold and fcc platinum [2022]. The calculated lattice constants (a Au = 4.076 Å and a Pt = 3.922 Å with uncertainties ~ 0.001 Å) were in a good agreement with lattice constants of Au and Pt nanoparticles known from the literature [23, 24].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These structural findings were confirmed by analysis of XRD standard Bragg reflections (Fig. 2b), which could be assigned to fcc gold and fcc platinum [2022]. The calculated lattice constants (a Au = 4.076 Å and a Pt = 3.922 Å with uncertainties ~ 0.001 Å) were in a good agreement with lattice constants of Au and Pt nanoparticles known from the literature [23, 24].…”
Section: Resultssupporting
confidence: 80%
“…The rings on SAED (Fig. 2a) patterns could be attributed to the (111), (200), (220), (311) and (222) lattice planes of Au and Pt nanocrystals with face-centered cubic lattice [20]. Due to the large size of the Pt NPs (> 140 nm), the SAED pattern should contain some spots, however it is formed of well-defined, continuous rings.…”
Section: Resultsmentioning
confidence: 99%
“…The surface Pt-rich bimetallic nanocatalysts with different Au/Pt atomic ratios have demonstrated enhanced hydrogenation selectivity or activity than AuPt alloys and monometallic Pt nanomaterials [20,21]. In addition, Au@Pt NPs showed the highest response current for the catalytic oxidation of glucose solution compared with those of Pt and Au NPs [22,23]. Recent theoretical predictions showed that the PtAu surface avoids the CO formation and apparently exhibits higher CO-poisoning tolerance when compared with the Pt@Pd surface [24].…”
Section: Introductionmentioning
confidence: 99%
“…From the SAED pattern, it was found that the obtained AuPt NCs have a crystalline structure (sharp diffraction rings with bright spots were observed). The diffraction rings ( Figure 3 d) could be attributed to the (111), (200), (220), and (311) lattice planes of Au and Pt nanocrystals crystalized in the face-centered cubic structure [ 34 ].…”
Section: Resultsmentioning
confidence: 99%